1995
DOI: 10.1007/bf00373908
|View full text |Cite
|
Sign up to set email alerts
|

On the regulation of the expressed L-type calcium channel by cAMP-dependent phosphorylation

Abstract: The Ca2+ channel subunits alpha 1C-a and alpha 1C-b were stably expressed in Chinese hamster ovary (CHO) and human embryonic kidney (HEK) 293 cells. The peak Ba2+ current (IBa) of these cells was not affected significantly by internal dialysis with 0.1 mM cAMP-dependent protein kinase inhibitor peptide (mPKI), 25 microM cAMP-dependent protein kinase catalytic subunit (PKA), or a combination of 25 microM PKA and 1 microM okadaic acid. The activity of the alpha 1C-b channel subunit expressed stably in HEK 293 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 31 publications
7
61
1
Order By: Relevance
“…This agrees with recent results by others [22] who showed that expression of L-type Ca 2+ channels in CHO or HEK cells were not sensitive to PKA. Again in agreement with our results, but in contrast to others [16,17], these authors could not observe double-pulse facilitation in artificially expressed L-type Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with recent results by others [22] who showed that expression of L-type Ca 2+ channels in CHO or HEK cells were not sensitive to PKA. Again in agreement with our results, but in contrast to others [16,17], these authors could not observe double-pulse facilitation in artificially expressed L-type Ca 2+ channels.…”
Section: Discussionsupporting
confidence: 93%
“…Despite much effort, it has not been possible to fully reconstitute ␤-adrenergic regulation or PKA regulation of holomeric Ca V 1.2 channels in nonmuscle cells (e.g., refs. [54][55][56]. Small increments in Ca V 1.2 channel activity have been observed, but typically Ͻ10% of the increases in I Ca that were observed in cardiac myocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of 13 may be necessary for a voltage-dependent facilitation of Ca 2+ channel current which, in turn, may be modulated by PKA [22]. However, most studies in expression systems do not support a role for the I] subunit, since coexpression of 13 with alc does not restore the positive modulation of the channel by PKA in Xenopus oocytes and in CHO cells and does not significantly alter the reducing effects of PKA inhibitors [20][21][22][23]. Our finding that the removal of a single PKA site in ~lC completely eliminates the effects of PKA inhibitors, and that the presence of the ~2A subunit does not restore these effects, also argues against the involvement of the 13 subunit in PKA modulation in the expression systems.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by the finding that PKA inhibitors reduce the Ca 2+ current via channels formed by C~lc alone or with some or all of the auxiliary subunits in CHO and HEK293 cells and in Xenopus oocytes [17,[20][21][22], suggesting that Cqc is the main target for this modulation. There is little doubt that the observed decrease in Ca 2--channel current is caused by dephosphorylation of PKA sites due to the activity of endogenous protein phosphatases, because the peptide and proteins used to inhibit PKA in these experiments are highly specific toward PKA [21].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation